2021
DOI: 10.3389/fimmu.2021.613979
|View full text |Cite
|
Sign up to set email alerts
|

The Cholinergic Drug Galantamine Alleviates Oxidative Stress Alongside Anti-inflammatory and Cardio-Metabolic Effects in Subjects With the Metabolic Syndrome in a Randomized Trial

Abstract: Background: The metabolic syndrome (MetS) is an obesity-associated disorder of pandemic proportions and limited treatment options. Oxidative stress, low-grade inflammation and altered neural autonomic regulation, are important components and drivers of pathogenesis. Galantamine, an acetylcholinesterase inhibitor and a cholinergic drug that is clinically-approved (for Alzheimer's disease) has been implicated in neural cholinergic regulation of inflammation in several conditions characterized with immune and met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 73 publications
(62 reference statements)
0
29
0
Order By: Relevance
“…In our study into the effects of medication on the oxidative/anti-oxidative status and mtDNA copy number, we found significant associations between AD patients using rivastigmine or galantamine and a lower serum TBARS level as well as increased mtDNA copy number. The reduction of TBARS level induced by cholinesterase inhibitors has previously been observed in both mouse and human studies; furthermore, it has been suggested that the reduction may inhibit disease progression [ 42 , 43 ]. Our study is the first to involve dementia patient observations to support this theory.…”
Section: Discussionmentioning
confidence: 99%
“…In our study into the effects of medication on the oxidative/anti-oxidative status and mtDNA copy number, we found significant associations between AD patients using rivastigmine or galantamine and a lower serum TBARS level as well as increased mtDNA copy number. The reduction of TBARS level induced by cholinesterase inhibitors has previously been observed in both mouse and human studies; furthermore, it has been suggested that the reduction may inhibit disease progression [ 42 , 43 ]. Our study is the first to involve dementia patient observations to support this theory.…”
Section: Discussionmentioning
confidence: 99%
“…These beneficial effects are associated with a decrease in insulin levels and alleviated insulin resistance [72,73]. In addition, analysis of heart rate variability reveals that galantamine treatment modulates the autonomic regulation and sympathovagal balance towards lower sympathetic and higher vagal activity [72,73] (Fig. 1).…”
Section: Current Clinical Exploration Of Vagus Nerve Stimulation and ...mentioning
confidence: 99%
“…Performing a clinical trial with galantamine in people with metabolic syndrome supported by findings from animal studies and the fact that this centrally acting acetylcholinesterase inhibitor is a clinically approved drug for Alzheimer's disease [23,84]. In a randomized, double-blind, placebo-controlled trial treatments of patients with the metabolic syndrome with relatively low galantamine doses (8 mg, escalated to 16 mg daily) for 12 weeks significantly suppressed plasma TNF and leptin levels, increased plasma adiponectin levels, and ameliorates oxidative stress [72,73 ▪▪ ]. These beneficial effects are associated with a decrease in insulin levels and alleviated insulin resistance [72,73 ▪▪ ].…”
Section: Neural Control Of Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no caution in place for the use of galantamine in people having mental health problems [ 12 ]. A randomized trial by Sangaleti et al [ 13 ] found that galantamine treatment reduces oxidative stress by increasing antioxidant enzyme activities which includes superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase [ 13 ]. Moreover, galantamine significantly alleviates insulin resistance reducing the risk of metabolic syndrome and cardiovascular diseases [ 13 ].…”
Section: Main Textmentioning
confidence: 99%